Lactobacillus rhamnosus GG colonization in early life regulates gut-brain axis and relieves anxiety-like behavior in adulthood. (March 2022) - Zhou, Bingqian; Jin, Ge; Pang, Xiaoqi; Mo, Qi; Bao, Jie; Liu, Tiaotiao; Wu, Jingyi; Xie, Runxiang; Liu, Xiang; Liu, Jinghua; Yang, Hongwei; Xu, Xin; et al.
Abstract: Evidence reveals that gut dysbiosis is involved in bidirectional interactions in gut-brain axis and participates in the progress of multiple disorders like anxiety. Gut microbes in early life are crucial for establishment of host health. We aimed to investigate whether early life probiotics Lactobacillus rhamnosus GG ( LGG ) colonization could relieve anxiety in adulthood through regulation of gut-brain axis. Live or fixed LGG was gavaged to C57BL/6 female mice from day 18 of pregnancy until natural birth, and newborn mice from day 1 to day 5 respectively. In this study, we found that live LGG could be effectively colonized in the intestine of offspring. LGG colonization increased intestinal villus length and colonic crypt depth, accompanied with barrier function protection before weaning. Microbiota composition by 16S rRNA sequencing showed that some beneficial bacteria, such as Akkermansia and Bifidobacteria, were abundant in LGG colonization group. The protective effect of LGG on gut microbiota persisted from weaning to adulthood. Intriguingly, behavioral results assessed by elevated plus mazed test and open field test demonstrated relief of anxiety-like behavior in adult LGG -colonized offspring. Mechanically, LGG colonization activated epithelial growth factor receptor (EGFR) and enhanced serotonin transporter (SERT) expression and modulated serotonergic system in the intestine, and increased brain-derived neurotrophic factor and γ-aminobutyric acid receptor levels in the hippocampus and amygdala. Blocking EGFR blunted LGG -induced the increased SERT and zonula occludens-1 expression. Collectively, early life LGG colonization could protect intestinal barrier of offspring and modulate gut-brain axis in association with relief of anxiety-like behavior in adulthood. Graphical Abstract: ga1 Highlights: LGG could be colonized in weaning offspring after early life supplement. Early life LGG colonization protected intestinal barrier of weaning offspring. Early life LGG colonization altered adult gut microbiota and microbial metabolites. Early life LGG colonization regulated intestinal serotonin tranporter and hippocampal gene expression. Early life LGG colonization alleviated adult anxiety-like behavior.